Development and usefulness of planning techniques and decision‐making foundations on the example of construction enterprises in Poland / Planavimo metodai ir sprendimų priėmimo pagrindai Lenkijos statybos įmonėse: naudingumas ir tobulinimas - Oleg Kapliński (Technological and Economic Development of Economy, 2008)
Three groups of planning techniques and foundations for decision‐making techniques have been identified. Their development tendencies have been indicated, as well as degree of practical usage by Polish construction companies. Two periods: the years 1990 and 2005 have been compared. Data and numbers have been obtained mainly by questionnaires and personal contacts. A relationship between the degree of utilisation of the discussed techniques and the type, size, and legal ownership of a construction company has not been found, in spite of current prosperity trends in the construction sector. A discrepancy between the evaluation of the degree of attractiveness of techniques and methods from the viewpoint of academics and building company managers has been pointed out.